Pembuatan Standard Operating Procedure (SOP) Pelaksanaan Pelayanan Sirkulasi Perpustakaan SMA Negeri 8 Padang - Feronza, Lidya; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discusses about making of the Standard Operating Procedure (SOP) Library SMAN 8 Padang in order to improve the quality of library services. With the SOP, the service quality standards that would be generated by a job can be measured in advance. Similarly, the expected quality of service provided to the user can be determined. The method used is descriptive method. Data were collected through direct observation and interviews to the Library of SMA 8 Padang. Interviews were conducted with staff at the school. Based manufacture Standard Operating Procedure (SOP) can be concluded that the SOP would make the rules applied in the library service can be run according to the SOP that has been made and when the students visit the library became more focused and does not violate the regulations set out in terms of service.Â Keyword: SOP, Services, Library.